Waste Treatment and Environmental Sustainability: Current Trends, Challenges and Management Strategies - Kumar, Sunil; Sharma, Pooja; Dutta, Deblina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Discover the latest advancements in waste management and environmental sustainability with "Waste Treatment and Environmental Sustainability: Current Trends, Challenges, and Management Strategies". This comprehensive reprint features research and review articles that delve into the pressing issues of waste treatment and offer innovative solutions for a more sustainable future. Improper waste management poses significant risks to the environment and human health. Traditional methods have proven inadequate, driving the need for alternative approaches. This reprint explores sustainable practices such as bioremediation, phytoremediation, and green technologies that reduce waste generation and optimize resource utilization. The Special Issue included in the reprint presents 11 articles covering diverse topics such as predicting O3 levels, COVID-19's impact on household waste, reverse logistics, data analytics in waste management, and the role of biochar in phytoremediation. These articles provide valuable insights and directions for future research. "Waste Treatment and Environmental Sustainability" is an essential resource for researchers, practitioners, and policymakers passionate about waste management and environmental preservation. Explore the latest research findings and discover innovative strategies to create a cleaner, healthier, and more sustainable world.